Produção e caracterização de complexos de carboximetil lignina metais a partir de lignina de bagaço de cana-de-açúcar e sua aplicação em estudos cinéticos de remoção de corantes de soluções aquosas - Silva, Leandro Gustavo da (2014)
In this work the lignin from the process Dedini s Rapid Hydrolysis (LD) was chemically modified by a carboxymethylation reaction that resulted in an anionic polyelectrolyte called carboxymethyl lignin (CMLD). The CMLD proved capable of complexing with metals in aqueous solution to form metallic aggregates (insoluble in water) Al3+ (CML-Al) and Mn2+ (CML-Mn). The CMLD, CML-Al and CML-Mn were characterized by measurements of Surface Area and Porosity, Fourier Transformed Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA) and Electron Microscopy (SEM). The CML-Al and the CML-Mn were used for removal of the reactive dye Procion Blue MX-R (PB) from aqueous solutions. Measurements of the pH of the isoelectric point (pHPZC) were determined for CML-Al and CML-Mn. The optimum pH established and the contact time were 2,0 and 5 hours, respectively. The kinetic and equilibrium data fit together better in the general order kinetic model and the isotherm model of Liu. The values obtained for the maximum adsorption capacity of CML-Al and CML-Mn at 25°C were 73,52 and 55,16 mg.g-1, respectively. Four cycles of adsorption/desorption experiments were performed attaining regenerations of up to 98.33% (CML-Al) and 98.08% (CML-Mn) from dye-loaded adsorbents, using 50% acetone + 50% of 0,05 mol L-1 NaOH. The CML-Al removed 93.97% while the CML-Mn removed 75.91% of dyes present in solutions simulating the effluent from textiles. The use of residues from biomass such as lignin for the production of new materials shows a promising way in the application of these biomaterials in various areas including as adsorbents.